Docetaxel, bevacizumab, and androgen deprivation therapy for biochemical disease recurrence after definitive local therapy for prostate cancer. Issue 15 (22nd April 2015) - McKay, Rana R.; Gray, Kathryn P.; Hayes, Julia H.; Bubley, Glenn J.; Rosenberg, Jonathan E.; Hussain, Arif; Kantoff, Philip W.; Taplin, Mary‐Ellen
<x xml:space="preserve">Abstract</x> BACKGROUND Patients with biochemical disease recurrence (BCR) after definitive treatment for prostate cancer comprise a heterogeneous population for whom standard therapy options are lacking. The purpose of the current trial was to evaluate the feasibility, toxicity, and efficacy of early multimodality systemic therapy in men with BCR. METHODS Eligible patients had an increasing prostate‐specific antigen (PSA) level, a PSA doubling time ≤10 months, and no evidence of metastases after radical prostatectomy (RP) and/or radiotherapy (RT) for localized disease. Treatment consisted of docetaxel at a dose of 75 mg/m2 every 3 weeks for 4 cycles, bevacizumab at a dose of 15 mg/kg every 3 weeks for 8 cycles, and androgen deprivation therapy (ADT) for 18 months. The primary endpoint was the percentage of patients who were free from PSA progression 1 year after the completion of therapy. RESULTS A total of 41 patients were included in the analysis. At 1 year after the completion of ADT, 45% of patients (13 of 29 patients) and 29% of patients (5 of 17 patients) with a testosterone level ≥100 ng/dL and ≥240 ng/dL, respectively, had a PSA <0.2 ng/mL. The median follow‐up was 27.5 months (interquartile range, 21.8‐38.1 months). Eight patients (20%) were free from PSA progression, 19 patients (46%) did not reinitiate ADT, and 34 patients (83%) were free from metastasis. Sixteen patients (39%) experienced grade 3 and 5 patients (12%) experienced grade 4 toxicities (toxicity was assessed using the National Cancer Institute Common Terminology Criteria for Adverse Events [version 3.0]). CONCLUSIONS Multimodality systemic therapy with docetaxel, bevacizumab, and ADT is feasible and produces PSA responses in men with BCR. Long‐term follow‐up is needed to determine the percentage of patients with a durable PSA response who are able to avoid having to reinitiate prostate cancer therapy. Cancer 2015;121:2603–2611. © 2015 American Cancer Society.